Answer:
x = -1
Explanation:
The usual approach to these is to square the radicals until they are gone.
![\displaystyle√(3x+7)+√(x+1)=2\\\\(3x+7) +2√((3x+7)(x+1))+(x+1) = 4\qquad\text{square both sides}\\\\2√((3x+7)(x+1))=-4x-4\qquad\text{subtract $4x+8$}\\\\(3x+7)(x+1)=(-2x-2)^2\qquad\text{divide by 2, square again}\\\\3x^2+10x +7=4x^2+8x+4\qquad\text{simplify}\\\\x^2-2x-3=0\qquad\text{subtract the left expression}\\\\(x-3)(x+1)=0\qquad\text{factor}\\\\x=3,\ x=-1\qquad\text{solutions to the quadratic}](https://img.qammunity.org/2021/formulas/mathematics/college/v5v6liy1tj65r6y6rma3joar95hcsvd6fw.png)
Each time the equation is squared, the possibility of an extraneous root is introduced. Here, x=3 is extraneous: it does not satisfy the original equation.
The solution is x = -1.
_____
Using a graphing calculator to solve the original equation can avoid extraneous solutions. The attachment shows only the solution x = -1. Rather than use f(x) = 2, we have rewritten the equation to f(x)-2 = 0. The graphing calculator is really good at showing the function values at the x-intercepts.